EFEKTIVITAS PELAYANAN PENERBITAN KARTU KELUARGA MELALUI TANDA TANGAN ELEKTRONIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SOLOK PROVINSI SUMATERA BARAT - Edtyva Dwirahmi Rizqiqa; Rizki Amalia (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2021)
Electronic signatures are an innovation of the population acceleration program, aimed at making population documents more efficient without having to meet face-to-face. There are still damaged documents in the issuance of family cards and the limited number of employees who understand services through electronic signatures are problems. The purpose of the study was to determine the effectiveness of family card issuance services through electronic signatures, obstacles and efforts to overcome them. The method used is descriptive qualitative inductive approach. Data collection techniques were carried out by triangulation which included in-depth interviews (10 informants), observation and documentation. In this paper, an analysis of the effectiveness of family card issuance services through electronic signatures is carried out with the indicators studied, namely (1) Production or productivity, (2) Quality, (3) Efficiency, (4) Flexibility, and (5) Satisfaction. (Gibson and Steers in Sumaryadi (2005:107)).The results showed that the effectiveness of family card issuance services through electronic signatures had been implemented quite well, but still needed improvements in efficiency indicators. Barriers to the effectiveness of family card issuance services through electronic signatures, namely (1) Unstable Network Connections, (2) Lack of Human Resources, (3) Lack of supporting facilities. Efforts are being made to overcome obstacles, namely (1) repairing the server network that is experiencing disruptions, (2) Involving existing employees in training or technical guidance, (3) Adding supporting facilities. Suggestions from the research: (1) reform the system related to optimizing the central network as the organizer of the Electronic Signature policy, (2) increase the number of employees and (3) improve infrastructure facilities. Keywords: Electronic Signature, Effectiveness, Family Card.